An Author’s Editor Reads the “Instructions for Authors” - Thomas A Lang (European Science Editing)
I’ve been a medical writer and author’s editor for 45 years. I have read the instructions for authors in dozens of medical journals. I know what authors (and author’s editors) think of these instructions, at least among those who know that journals actually have instructions for authors. For almost as long, I’ve been a member of four professional societies concerned with scientific publishing, and I know a lot of editors-in-chief of medical journals. I appreciate their desire to have authors follow the instructions when preparing manuscripts, at least among those editors who remember that their journals have such instructions and insist, at least occasionally, that they be followed.